Short- and Long-term Outcomes of One-stage Radical Resection and Anastomosis without Preoperative Decompression and Diverting Stoma between Incomplete Obstructive and Non-obstructive Left-sided Colorectal Cancer: A Retrospective Observational Study - Kentaro Sato; Yosuke Fukunaga; Manabu Takamatsu; Tatsuki Noguchi; Takashi Sakamoto; Shimpei Matsui; Toshiki Mukai; Tomohiro Yamaguchi; Takashi Akiyoshi (Journal of the Anus, Rectum and Colon)
Objectives: This study aimed to evaluate the safety and long-term outcomes of a one-stage resection and anastomosis approach without preoperative decompression in patients with left-sided incomplete obstructive colorectal cancer. Methods: We conducted a retrospective analysis of 571 patients diagnosed with pT3-4NanyM0 left-sided colorectal cancer who underwent radical resection and primary anastomosis without preoperative decompression or a diverting stoma from April 2012 to December 2019. Of these, 97 (17%) patients presented with incomplete obstruction, while 474 (83%) had no obstruction. Incomplete obstruction was characterized by the inability of a small-caliber endoscope to pass through the tumor without necessitating emergency surgery or decompression due to bowel obstruction. We compared perioperative short-term outcomes, as well as the 5-year overall survival rate and the 5-year relapse-free survival rate between the two groups. Results: Patients in the incomplete obstruction group experienced significantly longer median intervals between admission and surgery (6 vs. 2 days, P<0.001), higher complication rates (25.8% vs. 15%, P=0.016), and longer median postoperative hospital stays (10 vs. 9 days, P=0.002). However, the rates of anastomotic leakage (2.1% vs. 2.3%, P=1), the 5-year overall survival (91.5% vs. 93.7%, P=0.436), and the 5-year relapse-free survival (80.2% vs. 85.6%, P=0.195) were comparable between the groups. Conclusions: The outcomes regarding anastomotic leakage and long-term survival for one-stage resection and anastomosis without preoperative decompression in cases of incomplete obstructive colorectal cancer are promising. This management strategy appears feasible and safe with appropriate preoperative bowel preparation.